Community perception of malaria in a vulnerable municipality in the Colombian Pacific - Carol Yovanna Rosero; Gloria Isabel Jaramillo; Franco Andrés Montenegro; César García; Arelis Alexandra Coral (Malaria Journal, 2020)
Abstract Background Malaria primarily affects populations living in poor socioeconomic conditions, with limited access to basic services, deteriorating environmental conditions, and barriers to accessing health services. Control programmes are designed without participation from the communities involved, ignoring local knowledge and sociopolitical and cultural dynamics surrounding their main health problems, which implies imposing decontextualized control measures that reduce coverage and the impact of interventions. The objective of this study was to determine the community perception of malaria in the municipality of Olaya Herrera in the Colombian Pacific. Methods A 41-question survey on knowledge, attitudes, and practices (KAP) related to malaria, the perception of actions by the Department of Health, and access to the health services network was conducted. Results A total of 134 adults were surveyed, in whose households a total of 671 people lived. According to the survey data, about 80% of the household members included teenagers and children, out of which 61% had malaria at one time, and for 75.3%, this disease is a persistent problem. In spite of this, 57.2% of people who fell ill due to malaria were never visited by health personnel for a follow up. This population claimed that responsibility for who should prevent the disease is shared between each person and the Department of Health. However, personal actions were focused on using mosquito nets, ignoring other important practices to prevent bites. Despite campaigns by the Department of Health, 11.9% of respondents did not know how malaria was transmitted, and 8.96% thought it was transmitted through water. Also, 43.5% said that the Department of Health did not do any work to control malaria and 16% did not know if any action was taken. Conclusions In spite of the knowledge about malaria and the efforts of the Department of Health to prevent it, the community actions do not seem to be consistent with this knowledge, as the number of cases of malaria is ...